Quantitative evaluation of brittleness of deep shale gas reservoirs of Wufeng- Longmaxi formations in Lintanchang area, southeastern Sichuan Basin - Shaoke FENG; Liang XIONG; Shuai YIN; Xiaoxia DONG; Limin WEI (Shiyou shiyan dizhi)
With the increase in rock plasticity of deep shale gas reservoirs, their brittleness characteristics become difficult to be accurately characterized using traditional evaluation methods. Taking the deep shale gas reservoirs from the upper Ordovician Wufeng Formation to the first member of Lower Silurian Longmaxi Formation in the Lintanchang area of the southeastern Sichuan Basin as a case study, triaxial rock mechanics and fracture toughness experiments on shale samples were conducted. Based on the experimental results, a comprehensive quantitative evaluation of reservoir brittleness was carried out using deep learning. The experimental results showed that with the increasing temperature and pressure, the Young's modulus, Poisson's ratio, and compressive strength of the shale samples all increased. The brittleness of shale samples from layer ① was significantly lower than that of samples from layer ③. Shale samples with better brittleness exhibited obvious fluctuations in the stress-strain curves, showed nonlinear deformation characteristics, and had relatively small residual strain values. The fracture toughness of shale samples was closely related to the content of brittle minerals, and the fracture toughness values of type Ⅰ and type Ⅱ samples with laminations perpendicular to bedding planes were relatively lower. Based on the shale characteristics of mineral composition, triaxial rock mechanics, and fracture toughness, a deep learning weight analysis model was developed using brittleness indices Bel and Bmine3 and fracture toughness index IKIC as data inputs.The cumulative risk value was less than 5, indicating the high reliability of the model.A comprehensive brittleness index B was established based on the model, and its correlation with the measured brittleness index BS of core samples was significantly improved (R=0.852 7). The quantitative brittleness evaluation results truly reflect the vertical profile of brittleness characteristics in deep shale reservoirs. The reservoirs at layer ③ bottom and layer ② in the Wufeng-Longmaxi formations of the study area exhibit relatively better brittleness and lower fracture toughness index, making them preferred target layers for future exploration and development.